Association of extent of cannabis use and psychotic like intoxication experiences in a multi-national sample of first episode psychosis patients and controls. Issue 12 (28th September 2021) - Sami, Musa; Quattrone, Diego; Ferraro, Laura; Tripoli, Giada; Cascia, Erika La; Gayer-Anderson, Charlotte; Selten, Jean-Paul; Arango, Celso; Bernardo, Miguel; Tarricone, Ilaria; Tortelli, Andrea; Gatto, Giusy; et al.
Abstract: Background: First episode psychosis (FEP) patients who use cannabis experience more frequent psychotic and euphoric intoxication experiences compared to controls. It is not clear whether this is consequent to patients being more vulnerable to the effects of cannabis use or to their heavier pattern of use. We aimed to determine whether extent of use predicted psychotic-like and euphoric intoxication experiences in patients and controls and whether this differs between groups. Methods: We analysed data on patients who had ever used cannabis ( n = 655) and controls who had ever used cannabis ( n = 654) across 15 sites from six countries in the EU-GEI study (2010–2015). We used multiple regression to model predictors of cannabis-induced experiences and to determine if there was an interaction between caseness and extent of use. Results: Caseness, frequency of cannabis use and money spent on cannabis predicted psychotic-like and euphoric experiences ( p ⩽ 0.001). For psychotic-like experiences (PEs) there was a significant interaction for caseness × frequency of use ( p < 0.001) and caseness × money spent on cannabis ( p = 0.001) such that FEP patients had increased experiences at increased levels of use compared to controls. There was no significant interaction for euphoric experiences ( p > 0.5). Conclusions: FEP patients are particularly sensitive to increased psychotic-like, but not euphoric experiences, at higher levels of cannabis use compared to controls. This suggests a specific psychotomimetic response in FEP patients related to heavy cannabis use. Clinicians should enquire regarding cannabis related PEs and advise that lower levels of cannabis use are associated with less frequent PEs.